Web-based conference management system for higher learning institutions - Ahmad, Kamsiah; Abdullah, Aimi Amirah; Zeki, Akram M. (IIUM Press, 2015)
Online management system is very important nowadays in education (Hamad et al., 2011), recently many systems have been designed in this field to help the users to communicate online (Maimona et al, 2011; Akram et al., 2011; Akram et al., 2012). The Conference Management Online System is the system that will be used by Event Manager in order to manage conference papers that were submitted by the authors, examples of these systems are shown in previous research. In this study, the implementation of system features would provide an efficient submission of conference papers that will be arranged systematically which will be easier for users to understand. This study is about Conference Management Online System which provides an easier way of managing events when conducting a conference. The system will be specifically built for the convenience of Event Manager in managing online submission of papers and procedures with relation to the Event Manager himself, Reviewers and Authors. Besides that, this system is being proposed due to the lack of Conference Management Online System built especially for a university. This study would not only focus on the development process of the Conference Management Online System but it would also summarizes current system which are in use, design analysis of the new system which will include the flowchart of the systems and requirements needed in order to develop the system